PENGARUH CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI CAFE (STUDI KASUS MAHASISWA JURUSAN MANAJEMEN ANGKATAN 2019 STIENAS BANJARMASIN) - Mailiana, Mailiana; Hayati, Diana; Budiati, Penta Lestarini (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2023)
This research aims to determine the influence of brand image and price on purchasing decisions at Cafés (Case Study of 2019 Management Department Students at STIENAS Banjarmasin). The research population was all students of the 2019 Management Department at STIENAS Banjarmasin, totaling 137 people. Criteria for students who have visited the café at least twice. The sample in this study was 35 respondents. Data analysis processing uses SPSS for Windows version 26 with multiple linear regression tests. The results of the research found that the calculated t value of the brand image variable was 3,360 > t table of 1,692 with a significance level of 0.002 < 0.05, so it can be interpreted that the brand image variable has a partially significant effect on purchasing decisions in cafés. The calculated t value of the price variable is 2.109 > t table of 1.692 with a significance level of 0.043 < 0.05 so it can be interpreted that the price variable has a partially significant effect on purchasing decisions at the Café. The Fcount value in this study is 14.262 when compared with the Ftable value of 3.28, so it can be seen that Fcount > Ftable (14.262 > 3.28) and it turns out that Ho is rejected and Ha is accepted. The conclusions of this research are (1) Brand Image partially has a significant influence on purchasing decisions at Cafes (Case Study of 2019 Management Department Students at STIENAS Banjarmasin). (2) Price partially has a significant effect on purchasing decisions at cafes (Case Study of 2019 Management Department Students at STIENAS Banjarmasin). (3) Brand Image and Price simultaneously have a significant influence on purchasing decisions at Cafes (Case Study of 2019 Management Department Students at STIENAS Banjarmasin).